Bibliometric Mapping of Factors Influencing Compliance in Nursing Care Documentation - Sai'ah Sai'ah; Syamsul Arifin; Mohamad Isa; Meitria Syahdatina Noor; Lenie Marlinae (Universitas Malahayati Lampung, 2024)
ABSTRACT Accurate and complete nursing documentation plays an important role in ensuring the quality of nursing care and patient safety. However, adherence to documentation standards among nurses often remains a challenge that affects the overall quality of medical records and clinical interventions. This study was conducted to map research trends and factors affecting compliance in nursing documentation through a bibliometric analysis approach. The main objective of this study was to identify the main topics, key factors, as well as emerging publication trends related to nursing documentation compliance over the past few years. This study used the Publish or Perish application to collect 50 scientific articles published between 2016 and 2024, with keywords such as